P75 Saddle embolism induced syncope: a case report. (June 2019) - Quinn, Shauna; Sandys, Vicki; O'Riordan, Deirdre
Abstract : Introduction: Saddle pulmonary embolism is a life-threatening, clinically challenging diagnosis. Syncope is an uncommon presentation, which may be misdiagnosed. We report the case of a 17-year-old Caucasian girl with saddle embolism induced syncope. Case presentation: A 17-year-old girl, with no history of disease, was admitted to the emergency department following a 1 day history of two syncopal episodes on a background of left groin pain. She had been taking the COCP for 6 months for the treatment of acne. On admission, she became haemodynamically unstable with a BP 70/40, sinus tachy 150bpm and 83% oxygen saturations on room air. ECG demonstrated sinus tachy, RBBB and V1Q3. Doppler was positive for a left iliofemoral DVT. Urgent CTPA confirmed a massive saddle embolus, multiple right lower zone PE and increased right heart pressure. She was immediately transferred to IR where she had catheter-directed mechanical thrombolysis with 10 mg TPA bolus, 500 IU of heparin followed by an infusion of TPA 0.5 mg/hour. Follow-up pulmonary angiogram demonstrated marked interval improvement with no evidence of residual thrombus. An ECHO was performed showing normal LV systolic function and a negative bubble study. Her lupus screen was negative. She was treated with Heparin according to the SJH protocol and discharged on Apixaban with haematology follow-up. Discussion: The annual incidence of paediatric PE is 0.5/10, 000. Diagnosis may be delayed in young individuals, with some reporting a median of 7 days from presentation to diagnosis. Prompt diagnosis is vital to broaden management options and decrease mortality. This is the case of a young woman presenting with a clear indication for thrombolysis. Correct recognition and appropriate use of catheter directed thrombolysis was life-saving. Research indicates that it may be considered in patients with persistent haemodynamic instability, those at risk of death before systemic therapy can be effective and those with high bleeding risks. Conclusion: Pulmonary embolism is an important differential in patients presenting with syncope, with many of these having a large or saddle embolus. Early identification is vital to avoid haemodynamic compromise and to optimise survival.